2005
DOI: 10.1037/1528-3542.5.3.354
|View full text |Cite
|
Sign up to set email alerts
|

Acute cortisol elevations cause heightened arousal ratings of objectively nonarousing stimuli.

Abstract: To test the effects of cortisol on affective experience, the authors orally administered a placebo, 20 mg cortisol, or 40 mg cortisol to 85 men. Participants' affective responses to negative and neutral stimuli were measured. Self-reported affective state was also assessed. Participants in the 40-mg group (showing extreme cortisol elevations within the physiological range) rated neutral stimuli as more highly arousing than did participants in the placebo and 20-mg groups. Furthermore, within the 20-mg group, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 34 publications
7
27
0
1
Order By: Relevance
“…Analyses revealed that high activity of both components of stress response was strongly associated with maximal learning performance. This observation reinforces the claim that both HPA axis activation and NE release are required for an optimal effect on learning (Roozendaal et al 1996(Roozendaal et al , 2006Cahill et al 2003;Okuda et al 2004;Abercrombie et al 2005) and supports the concept of convergence in time and space formulated by Joels et al (2006).…”
Section: Learning and Memory 331supporting
confidence: 86%
“…Analyses revealed that high activity of both components of stress response was strongly associated with maximal learning performance. This observation reinforces the claim that both HPA axis activation and NE release are required for an optimal effect on learning (Roozendaal et al 1996(Roozendaal et al , 2006Cahill et al 2003;Okuda et al 2004;Abercrombie et al 2005) and supports the concept of convergence in time and space formulated by Joels et al (2006).…”
Section: Learning and Memory 331supporting
confidence: 86%
“…4, available at www.jneurosci.org as supplemental material). These negative findings in mice are interesting in light of previous findings that glucocorticoids increase anxiety/arousal in human subjects (Abercrombie et al, 2005). It may be that our tests of anxiety in rodents are not as sensitive as measures in human studies.…”
Section: Resultsmentioning
confidence: 64%
“…Evidence with regard to GC effects on emotionally arousing stimuli is contradicting. One study found that GC administration caused heightened arousal in response to neutral stimuli without effects on mood (Abercrombie et al, 2005), whereas one other study found GCs to be mood uplifting (Het and Wolf, 2007). Fearreducing effects of GCs have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It could therefore be argued that GC administration leads to less interference from emotional distractions. GC administration, however, might also lead to more interference from neutral stimuli, if indeed these stimuli would become more arousing, although the evidence for this option is sparse (Abercrombie et al, 2005). Nonetheless, in both cases the distinction between neutral and emotional distraction would be less prominent.…”
Section: Introductionmentioning
confidence: 99%